2020
DOI: 10.1590/2175-7860202071014
|View full text |Cite
|
Sign up to set email alerts
|

Ramet demography of Aechmea distichantha (Bromeliaceae) in two contrasting years in the understory and open areas of a South American xerophytic forest

Abstract: The Schinopsis balansae forests of the Wet Chaco are characterized by convex areas with woody vegetation and plain areas with herbaceous vegetation. In the Wet Chaco, Aechmea distichantha is a terrestrial bromeliad that forms dense colonies in the understory and open areas of these forests. The aim of this study was to analyze the spatial and temporal variations in population dynamics of this bromeliad species. We monitored ramets growing in sun and shade conditions during two contrasting years. We analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…(Mondragón et al 2004), in Aechmea distichantha Lem. (Barberis et al 2020) and in D. brevifolia Rogalski et al 2017) Our results confirm Harper's review (1977) of the dynamics of perennial herbaceous populations, suggesting that recruitment via seeds contributes little to the maintenance of populations. Plants with sexual origin have a higher mortality rate and lower levels of success in the establishment (Zhang & Zhang 2007).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…(Mondragón et al 2004), in Aechmea distichantha Lem. (Barberis et al 2020) and in D. brevifolia Rogalski et al 2017) Our results confirm Harper's review (1977) of the dynamics of perennial herbaceous populations, suggesting that recruitment via seeds contributes little to the maintenance of populations. Plants with sexual origin have a higher mortality rate and lower levels of success in the establishment (Zhang & Zhang 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Drought was considered the main cause of death during the early stages of development of epiphytic bromeliads (Benzing 1981;Mondragón et al 2004; Rodriguésia 72: e00752020. 2021 Zotz et al 2005), as well, very low temperatures in A. distichantha (Barberis et al 2020). In the case of D. ibiramensis, besides lack of water, lack of nutrients and floods may also cause death, because they are not yet attached to the rock.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this study, it was found that rosettes in full sun were smaller (diameter of rosettes) than those under the 'sarandis' (shrubs of thin and exible stems of the banks of rivers) (J. M. Rogalski, personal observation). According Barberis et al (2020) for vegetative ramets, plant survival was higher in the shade than in the sun; and the higher owering of ramets in the shade is probably associated with milder conditions in the understory.…”
Section: Discussionmentioning
confidence: 96%
“…The disposition of the foliar bases produces a well-developed phytotelma that allows the accumulation of water and litter (Cavallero et al, 2009(Cavallero et al, , 2011, where a diverse aquatic community develops (Montero et al, 2010). This species mainly reproduces asexually, but sexual reproduction ensures the colonization of new patches (Barberis et al, 2014(Barberis et al, , 2020Brown, 1990). It is pollinated by birds and insects (Bianchi et al, 2000;Freire et al, 2018), and its fruits are consumed and dispersed by birds and mammals (Blendinger et al, 2015).…”
Section: Study Speciesmentioning
confidence: 99%